Evaluation of the Implementation of a Pedagogical Deep Learning Pilot Project Based on Islamic Values to Support the Kurikulum Merdeka in Elementary Schools - Reylita Rahmawanti; Feri Riski Dinata (Bulletin of Indonesian Islamic Studies, 2025)
The implementation of Kurikulum Merdeka (Independent Curriculum) emphasizes contextual and meaningful learning as well as the strengthening of the Profil Pelajar Pancasila. However, empirical research on integrating Islamic values into a deep learning pedagogy within this curriculum remains limited. Addressing this gap, this study aims to: (1) evaluate the implementation of an Islamic-values-based deep learning approach in elementary education, (2) identify the forms of Islamic value internalization that emerge during the learning process, and (3) formulate challenges and recommendations for strengthening teacher competence. This descriptive qualitative study involved three teachers and 32 students at SDN 01 Pisang Baru, Lampung, using in-depth interviews, participatory observations, and document analysis. The findings indicate that the model effectively promotes reflective and collaborative learning and supports the internalization of Islamic values—such as honesty, responsibility, and empathy—through socially contextualized project activities. Teachers act as facilitators who connect academic concepts with the practical application of Islamic teachings. Nevertheless, several constraints were identified, including limited project time and teachers’ insufficient mastery of character-based authentic assessment. The study contributes theoretically by providing an empirical framework for integrating Islamic values into deep learning pedagogy within Kurikulum Merdeka, and practically by offering recommendations to improve teacher professionalism in 21st-century learning.